Comparison of Dose Distribution with Graphical Optimization and Inverse Planning Techniques in Cervical Cancer Brachytherapy - Ni Nyoman Ratini; I Putu Wesa Angga Jaya; Gusti Ngurah Sutapa; I Putu Tedy Indrayana; Ni Putu Yuni Nurmalasari; I Wayan Balik Sudarsana (Jurnal Penelitian Pendidikan IPA, 2026)
Cervical cancer is the leading cause of death among women in Indonesia, with 36,964 new cases reported in 2022. Brachytherapy is a key component in treating advanced-stage cervical cancer, where dose optimization is critical to maximize the target dose (HRCTV) and minimize exposure to organs at risk. Graphical Optimization (GrO) and Inverse Planning (IP) techniques are commonly used, but comparative studies using Co-60 sources remain limited. Previous studies have largely used Ir‑192, so this study explores the comparison of GrO versus IP using Co‑60, which has not been widely studied in Indonesia. Co‑60 was chosen because it provides a dose distribution comparable to Ir‑192, has a longer half‑life reducing the frequency of source replacements and maintenance costs and has been reported to shorten patient treatment time by approximately 10%. This study compared the dose distribution of both techniques in 30 brachytherapy patients treated with a Co-60 source at Prof. Dr. I.G.N.G. Ngoerah Hospital. Data were analyzed using the Sagiplan 2.2.1 Treatment Planning System (TPS) following the TG-43 protocol. Evaluations included D90 HRCTV, COIN, DHI, bladder D2cc, and rectum D2cc based on ICRU Report 89 recommendations. MANOVA results (SPSS 29.0; significance < 0.05) showed that GrO’s D90 HRCTV (7.239 Gy ± 0.134 Gy) was significantly higher (sig = 0.006) than IP (7.155 Gy ± 0.093 Gy). GrO’s DHI (0.352 ± 0.043) was also superior (sig = 0.030), while COIN, bladder D2cc, and rectum D2cc showed no significant differences. Overall dose distribution for GrO differed significantly from IP (p = 0.011), though all parameters met ICRU standards. Conclusion: GrO excels in target coverage and homogeneity, while IP is equivalent in OAR protection. Both techniques are dosimetrically feasible, but GrO is more adaptive for complex anatomies despite requiring longer planning time.